Physiomic classification of vegetation in the municipality of Vitória da Conquista – Bahia - Santos, Vilmar Joaquim Dos; Nóbrega, Marcelo Araújo da (Seven Editora, 2023)
This research aimed to map and classify the phytophysiognographics de part of the municipality of Vitória da Conquista-BA, specifically the central portion where the city is located. It aimed to identify the main fragments of vegetation, also the different aspects of the current landscape using the LANDSAT 8 satellite images and the mapping of these variables. This research had a qualitative background character, a photographic survey was carried out in the period of 1 year and a half and associated with satellite images. The region analyzedis in a transition area between the Caatinga biome and the Atlantic Forest biome, regionally called theCípó Forest, for some a separate biome, that is, dry forest biome. It is an important study because it is an unrepresentative area in the national territory. In the course of the analysis within the municipality of Vitóri da Conquista, a variety of phytophysiognomy was found , such as the deciduous seasonal forest, semidecidual, areas of low forest between caatinga and cerrado, caatinga and deciduous forest and the shrub-tree caatinga. This gamma diversity is due to a gradient of climatic, geomorphological and lithological variables mainly. All vegetation is entirely uncharacterized and degraded with an intensepredominance of pasture, as well as areas with coffee and eucalyptus, a fact that is due to the expansion of private rural properties. DOI:https://doi.org/10.56238/devopinterscie-163